Stratigraphy, composition and age of Cuban rudist-bearing deposits - Reinaldo Rojas; Manuel Iturralde-Vicent; Peter W. Skelton (Revista Mexicana de Ciencias Geológicas)
Along the NE flank of Cuba, parts the Bahamian carbonate platform are exposed, while in the central part of the island a Cretaceous volcanic arc sequence is present. Rudist assemblages are found in both of these major tectonic settings… in order to continue, download the full paper in PDF.